Lung deposition patterns of MWCNT vary with degree of carboxylation. Issue 2 (7th February 2019) - Holian, Andrij; Hamilton, Raymond F.; Wu, Zhequion; Deb, Sanghamitra; Trout, Kevin L.; Wang, Zhiqian; Bhargava, Rohit; Mitra, Somenath
Abstract: Functionalization of multi-walled carbon nanotubes (MWCNT) is known to affect the biological response (e.g. toxicity, inflammation) in vitro and in vivo . However, the reasons for these changes in vivo are not well described. This study examined the degree of MWCNT functionalization with regard to in vivo mouse lung distribution, particle retention, and resulting pathology. A commercially available MWCNT (source MWCNT) was functionalized (f-MWCNT) by systematically varying the degree of carboxylation on the particle's surface. Following a pilot study using seven variants, two f-MWCNT variants were chosen and for lung pathology and particle distribution using oropharyngeal aspiration administration of MWCNT in Balb/c mice. Particle distribution in the lung was examined at 7 and 28 days post-instillation by bright-field microscopy, CytoViva hyperspectral dark-field imaging, and Stimulated Raman Scattering (SRS) microscopy. Examination of the lung tissue by bright-field microscopy showed some acute inflammation for all MWCNT that was highest with source MWCNT. Hyperspectral imaging and SRS were employed to assess the changes in particle deposition and retention. Highly functionalized MWCNT had a higher lung burden and were more disperse. They also appeared to be associated more with epithelial cells compared to the source and less functionalized MWCNT that were mostly interacting with alveolar macrophages (AM). These results showing a slightly reduced pathology despite the extended deposition have implications for the engineering of safer MWCNT and may establish a practical use as a targeted delivery system.